Development of a management model for the provision of long-term care services for elderly and disabled citizens on an extraterritorial basis - F. G. Myshko (Вестник университета)
Universal globalization dictates the need for new forms and methods of social work. The system of long-term care for elderly citizens and the disabled also requires updating. Basically, long-term care is based on regional regulation. The regions independently determine the list of “care” services, their volume, frequency and criteria of need. This gives rise to some kind of discrimination of some elderly citizens against others in terms of the volume and list of social services. In addition, the regional or decentralized principle of building a long-term care system «binds» elderly citizen in need of it to their place of residence, restricts their constitutional right to movement and freedom to choose their place of residence. The study analyzes the current state of regulation of the long-term care system and formulates proposals for the transition to the extraterritorial principle.